EDUCATIONAL THEORY APPLICATION IN HISTORY LEARNING - Elfa Michellia Karima; Firza; Wahidul Basri; Feni Astriani (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2021)
The purpose of this research is to determine how applying behavioristic learning theory, constructivist theory, humanistic theory, and cognitive theory to learning history at SMAN 1 Padang affects learning. In the learning process, learning theory is used as a reference. A theory can change or develop over time if there is a more complex or better theory for use in learning. Using this learning theory, learning objectives can be met while also improving educational quality. Improving educational quality can be accomplished by enhancing the teaching and learning process, analyzing student learning outcomes, and resolving classroom issues. In this study, survey and interview methods were used. The questionnaire asks 54 respondents six questions about the impact on the student learning process, specifically the History subject at SMAN 1 Padang. The variety of learning methods and theories used in learning allows students to maximize their ability to understand history.